2009
DOI: 10.1016/j.toxlet.2009.06.849
|View full text |Cite
|
Sign up to set email alerts
|

BC nanofibres: In vitro study of genotoxicity and cell proliferation

Abstract: Nanomaterials have unusual properties not found in the bulk materials, which can be exploited in numerous applications such as biosensing, electronics, scaffolds for tissue engineering, diagnostics and drug delivery. However, research in the past few years has turned up a range of potential health hazards, which has given birth to the new discipline of nanotoxicology. Bacterial cellulose (BC) is a promising material for biomedical applications, namely due its biocompatibility. Although BC has been shown not to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 44 publications
7
67
1
1
Order By: Relevance
“…This finding is consistent with previous data on the toxicity of cellulose fibers with a diameter of >100 nm (i.e., nonnano-objects), 16 as well as those on bacterial cellulose. 14 The latter showed no alteration to the viability of CHO or 3T3 fibroblast cells when treated with cellulose dispersions at concentrations of up to 0.1 mg 3 mL À1 for 72 h. A significant (p < 0.05) dose-dependent toxicity was, however, observed for CCN concentrations of 0.015 and 0.03 mg 3 mL À1 on the apical side of the triple cell coculture model. No adsorption of the LDH enzyme with the CCNs, MWCNTs, or CAFs was observed for any of the concentrations explored.…”
Section: ' Results and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This finding is consistent with previous data on the toxicity of cellulose fibers with a diameter of >100 nm (i.e., nonnano-objects), 16 as well as those on bacterial cellulose. 14 The latter showed no alteration to the viability of CHO or 3T3 fibroblast cells when treated with cellulose dispersions at concentrations of up to 0.1 mg 3 mL À1 for 72 h. A significant (p < 0.05) dose-dependent toxicity was, however, observed for CCN concentrations of 0.015 and 0.03 mg 3 mL À1 on the apical side of the triple cell coculture model. No adsorption of the LDH enzyme with the CCNs, MWCNTs, or CAFs was observed for any of the concentrations explored.…”
Section: ' Results and Discussionmentioning
confidence: 84%
“…Nevertheless, the dimensions and structure of individualized cellulose nanowhiskers (∼10À30 Â ∼100À2000 nm, depending upon the source) are vastly different from those of the microfibrillated cellulose (entangled fibers with a length of several micrometers) that was studied before. 1,14 Furthermore, cellulose degradation occurs primarily through enzymatic processes, which normally does not occur in the human body. One must also consider that surface-modified cellulose nanowhiskers are frequently used for nanocomposite fabrication.…”
Section: ' Introductionmentioning
confidence: 99%
“…In fact, in a particular investigation nanofi bers were produced from bacterial cellulose by a combination of acid and ultrasonic treatment. The genotoxicity of nanofi bers from bacterial cellulose was analyzed in vitro , using techniques previously demonstrated to detect the genotoxicity of fi brous nanoparticles [3] . The results of investigations involving among others single -cell gel electrophoresis and Salmonella reversion assays showed that nanofi bers do not display genotoxicity under the conditions tested.…”
mentioning
confidence: 99%
“…Bacterial cellulose nanofibres (BC-NF) 3T3 fibroblasts, CHO cells mutagenicity, proliferation, genotoxicity [103] Bacterial cellulose nanofibres HUVEC, C57/Bl6 mice viability, cytotoxicity, apoptosis/necrosis, cell cycle [104] Cellulose nanocrystals (CNCs) CNCs isolated from cotton, flax, hemp V79 fibroblast, Sf9 cells Cytotoxicity [110] Cotton cellulose nanofibres (CNF) Bovine fibroblasts cytotoxicity, stress response, apoptosis [111] CNCs isolated from cotton BEAS 2B cells, monocyte-derived macrophages cytotoxicity, genotoxicity, inflammatory response [112] CNCs isolated from MCC NIH3T3 fibroblasts, HCT116 cells cell viability [113] CNFs isolated from cotton Chlorella vulgaris cell viability, growth [114] CNCs isolated from wood C57BL/6 mice pulmonary outcome [115] Whilst the specific mechanisms associated with and driving any of the observed biochemical and biomolecular reactions measured are a necessity, it is vital that a specific understanding of how nanocellulose interacts with different biological systems can be developed, and how this relates to the biochemical response measured. The use of state-of-the-art microscopy approaches will be necessary due to the innate difficulties in identifying nanocellulose within cellular structures.…”
Section: Nanocellulose Form Studied Biological Model Used Endpoint Asmentioning
confidence: 99%